A method for improving the performance of silicon carbide ceramic 3D printing products
By using a combination of silicon carbide composite powder and phase change composite materials in silicon carbide ceramic 3D printing, and using ball milling, centrifugal spray granulation and sintering technologies, the problem of defects easily occurring in silicon carbide ceramics during the processing process has been solved and achieved. High mechanical strength and thermal stability of the product.
Patent Information
- Application Number
- CN202411205693.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-30
AI Technical Summary
Silicon carbide ceramics are prone to defects during processing, making it difficult to make components with complex geometric shapes. In 3D printing technology, the uniform distribution and density differences in powders affect product quality.
By mixing silicon carbide composite powder, phase change composite materials, binders, plasticizers, defoaming agents, water reducing agents and additives, ball milling, centrifugal spray granulation and screening, combined with sintering and 3D printing technology, Finally, pretreatment and annealing are performed in a gas pressure furnace to ensure the uniformity and density of the product.
It reduces the sintering temperature of silicon carbide powder, improves the uniformity of particle size and strength of powder particles, improves printing density and sintering density, and improves the mechanical strength and thermal stability of the product.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of silicon carbide ceramic preparation, and in particular to a method for improving the performance of silicon carbide ceramic 3D printed products. Background Art
[0002] The demand for silicon carbide ceramic structural parts in various new application scenarios is gradually increasing. For example, large-scale and complex-shaped silicon carbide ceramic nuclear reactor cores in the nuclear industry; silicon carbide ceramic workpiece tables, guide rails, reflectors, ceramic suction cups, arms, etc. of photolithography machines, key equipment for integrated circuit manufacturing; mid-to-high-end precision silicon carbide ceramic structural parts for the production of new energy lithium batteries; high-end precision silicon carbide ceramic structural parts for diffusion furnaces in the photovoltaic industry and precision high-purity silicon carbide ceramic structural parts for the production process of high-end chips in electronic semiconductors.
[0003] However, since silicon carbide is a covalent bond compound with a very strong Si-C bond, its hardness is second only to diamond. It is hard and brittle, and is prone to defects during processing. Silicon carbide ceramic components with complex geometric shapes are often difficult to manufacture using traditional processing techniques. This largely restricts the application of complex structured silicon carbide ceramics. 3D printing technology can effectively solve this problem.
[0004] The current mainstream process for preparing silicon carbide ceramics by binder jet 3D printing is to directly mix silicon carbide with a curing agent, and then use spray furan resin to solidify and form a blank, or to use spray granulation to strengthen the sphericity and improve the fluidity of the powder before printing. The above methods are limited by equipment and particles. The C in the process of making the blank cannot be evenly distributed. After sintering, there is a large density difference between the inside and outside of the blank, which affects the product quality. Summary of the invention
[0005] In order to improve the product quality of silicon carbide ceramics, the present application provides a method for improving the performance of silicon carbide ceramic 3D printed products.
[0006] The present application provides a method for improving the performance of silicon carbide ceramic 3D printing products using the following technical solutions:
[0007] A method for improving the performance of silicon carbide ceramic 3D printing products, comprising the following steps:
[0008] S1, mixing and ball-milling the silicon carbide composite powder, the phase change composite material, the binder, the binder, the plasticizer, the defoamer, the water reducing agent and the additive to obtain a slurry;
[0009] S2, subjecting the slurry to centrifugal spray granulation treatment to obtain treated powder;
[0010] S3, sieving the treated powder and retaining the powder with a mesh size of 120-200;
[0011] S4, sintering the screened powder;
[0012] S5, mixing the sintered powder with a curing agent and furan resin, and 3D printing to obtain a green blank;
[0013] S6, filling the formed green billet with nitrogen in a pressure furnace to maintain negative pressure conditions, so that moisture and organic matter in the green billet can be discharged smoothly to obtain a pretreated green billet;
[0014] S7, heating the green blank, burying silicon around the green blank, heating until the temperature reaches the melting point of silicon, keeping the temperature, heating it again, maintaining the temperature and then cooling it down, maintaining the temperature after cooling down to anneal the blank, and completing sintering to obtain 3D printed silicon carbide ceramics.
[0015] By adopting the above technical solution, after adding additives, the sintering temperature of silicon carbide powder can be reduced, so that the uniformity of particle size can be improved after sintering, thereby improving the strength of powder particles; using binder jet printing, the pore distribution range of the channel during 3D printing becomes narrower, which can make carburizing and siliconizing more uniform, thereby improving the printing density and sintering density, and improving the mechanical strength of the product; at the same time, adding phase change composite materials to the system can further improve the overall temperature resistance of the system and make it more stable during the sintering process.
[0016] Preferably, the silicon carbide composite powder comprises a composite of ultrafine silicon carbide powder and zinc oxide.
[0017] By adopting the above technical solution, the mechanical properties of the products obtained by 3D printing can be effectively improved by combining ultrafine silicon carbide powder with zinc oxide composite. The particle synergy between the ultrafine silicon carbide powder and the zinc oxide composite improves the compatibility and interfacial adhesion of the silicon carbide composite powder in the system, thereby improving the quality of the product.
[0018] Preferably, the zinc oxide composite comprises modified nano zinc oxide and boron nitride nanotubes.
[0019] Preferably, the modified nano zinc oxide is prepared by the following method:
[0020] Boron powder, iron oxide and ammonium chloride are mixed, heated and maintained, then washed to remove impurities, and then dried to obtain boron nitride nanotubes; hexadecyltrimethylammonium bromide is mixed with water, boron nitride nanotubes and nano zinc oxide are added after ultrasonic treatment, stirred and freeze-dried to obtain modified nano zinc oxide.
[0021] By adopting the above technical scheme, the modified nano zinc oxide and boron nitride nanotubes are compounded, which synergistically improves the mechanical properties of the system and can improve the strength of the binder. At the same time, the prepared zinc oxide composite has a small particle size, a large specific surface energy, and a high surface energy, and can fully combine with each component in the system, thereby improving the connection effect between the components and further improving the quality of the prepared product.
[0022] Preferably, the mass ratio of the zinc oxide composite to the silicon carbide ultrafine powder is 1:(0.25-0.33).
[0023] By adopting the above technical solution, the mass ratio between the zinc oxide composite and the silicon carbide ultrafine powder is preferably within the above range, which can further improve the overall stability of the silicon carbide powder composite.
[0024] Preferably, the phase change composite material comprises urea, melamine and n-octadecane.
[0025] Preferably, the phase change composite material is prepared by the following method:
[0026] Under water bath conditions, urea, melamine and formaldehyde solution are mixed, the pH value of the system is adjusted to alkaline, stirring is maintained, and water is added and stirred after cooling to obtain a prepolymer material; under water bath conditions, n-octadecane is mixed with a composite emulsifier, water is added and stirred, and ultrasonic treatment is performed after cooling to obtain an emulsion system; under oil bath conditions, the prepolymer material is mixed with the emulsion system, the system is adjusted to acidic after stirring, the temperature is increased and the stirring reaction is continued, centrifugation is performed after cooling, and the phase change composite material is obtained after washing and drying.
[0027] By adopting the above technical scheme, melamine and urea-formaldehyde resin are used as wall materials, and n-octadecane is used as core material. A phase change composite material is prepared by in-situ polymerization. The prepared phase change composite material has good stability. At the same time, the use of a composite emulsifier can increase the aggregation resistance of emulsion droplets during thermal motion, so that the prepared phase change composite material has good dispersibility, which effectively improves the stability of the prepared product.
[0028] Preferably, the emulsifier includes Span 80, Tween 80 and sodium lauryl sulfate.
[0029] By adopting the above technical solution, the phase change composite material prepared using the composite emulsifier is spherical in morphology, uniform in particle size, and has good stability. At the same time, the system can have good thermal stability and store energy during the preparation process to improve the quality of products prepared by 3D printing.
[0030] Preferably, the mass ratio of Span 80, Tween 80 and sodium dodecyl sulfate is 5.67:(5.8-6.4):1.
[0031] By adopting the above technical solution, preferably the mass ratio of Span 80, Tween 80 and sodium dodecyl sulfate is within the above range, which can effectively improve the stability of the prepared phase change composite material.
[0032] Preferably, the mass ratio between the silicon carbide composite powder and the auxiliary agent is 1:(0.12-0.18).
[0033] By adopting the above technical solution, the mass ratio between the silicon carbide composite powder and the additive is preferably within the above range, which can effectively improve the product quality of the prepared silicon carbide ceramic.
[0034] In summary, the present application includes at least one of the following beneficial technical effects:
[0035] After adding sintering aids, the sintering temperature of silicon carbide composite powder can be reduced, and the particle size can be made more uniform, thereby improving the bonding performance of silicon carbide composite powder. The powder shrinks and solidifies, and cracks organic matter to increase the carbon content in the powder. At the same time, C reacts with silicon to form β-SiC grains, which expand during the reaction and fill the gaps, making the components more closely bonded, thereby effectively improving the uniformity and quality of the product. At the same time, adding phase change composite materials to the system makes silicon carbide ceramics more stable during sintering.
[0036] Silicon carbide composite powder is obtained by compounding silicon carbide ultrafine powder and zinc oxide composite. The synergistic effect of micro-nano particles between silicon carbide ultrafine powder and zinc oxide composite can further improve the compatibility and interfacial adhesion of silicon carbide composite powder in the system, so that each component in the system can be fully combined, thereby further improving the product quality.
[0037] The phase change composite material prepared by urea, melamine and n-octadecane can effectively improve the overall thermal stability of the system, and the phase change composite material prepared by the composite emulsifier has good dispersibility and can improve the product quality of silicon carbide ceramics. DETAILED DESCRIPTION
[0038] The present application is further described in detail below with reference to the embodiments:
[0039] Raw material description: All raw materials in the examples can be obtained from commercial sources. Among them, the dispersant is polyvinyl alcohol (CAS No.: 9002-89-5); the binder is polyvinyl butyral (CAS No.: 63148-65-2); the plasticizer is dibutyl phthalate (CAS No.: 84-74-2); the defoamer is polysiloxane (CAS No.: 63148-62-9); the water reducer is acrylamide (CAS No.: 79-06-1); and the curing agent is methyl hexahydrophthalic anhydride (CAS No.: 25550-51-0). Example 1
[0040] Preparation of phase change composite materials:
[0041] In a water bath at 70°C, 5 g of urea (CAS No.: 57-13-6), 8 g of melamine (CAS No.: 108-78-1) and 12 g of a 37% formaldehyde solution were mixed, 30 g of deionized water was added, and the pH value of the system was adjusted to 8 using triethanolamine. The mixture was stirred at a speed of 300 r / min for 1 hour, then cooled to 25°C, and 20 g of deionized water was added and stirred for 10 minutes to obtain a prepolymer material. 9.09 g of Tween 80 (CAS No.: 9005-65-6), 9.31 g of Span 80 (CAS No.: 1338-43-8) and 1.6 g of sodium sulfate were mixed to obtain a composite emulsifier. In a water bath at 80°C, 5 g of n-octadecane (CAS No.: 593-45-3 ) was mixed with a composite emulsifier, 20 g of deionized water was added, and the mixture was stirred at a speed of 300 r / min for 10 min. 10 g of deionized water was continued to be added, and the mixture was stirred for 20 min. After cooling to 25°C, the mixture was ultrasonicated for 20 min to obtain an emulsion system. Under an oil bath condition of 60°C, 22 g of the prepolymer material was mixed with 18 g of the emulsion system, and the mixture was stirred at a speed of 600 r / min for 30 min. A citric acid solution with a mass fraction of 10% was added to adjust the pH value of the system to 2.5. After stirring for 30 min, the mixture was heated to 90°C, and the stirring reaction was continued for 2 h. After cooling to 25°C, the mixture was centrifuged at a speed of 200 r / min for 10 min. After filtration, the mixture was washed alternately with deionized water and anhydrous ethanol for 3 times, and dried in a vacuum drying oven at 40°C for 8 h to obtain a phase change composite material.
[0042] Preparation of modified nano zinc oxide:
[0043] Boron powder, iron oxide and ammonium chloride were mixed in a molar mass ratio of 2:1:1, heated at 600°C for 16 hours, washed alternately with hydrochloric acid and deionized water to remove impurities, and then vacuum dried at 65°C for 4 hours to obtain boron nitride nanotubes; 8.5g of hexadecyltrimethylammonium bromide (CAS No.: 57-09-0) was mixed with 600g of deionized water, ultrasonicated for 3 minutes, and then 10g of boron nitride nanotubes and 40g of nano zinc oxide were added, stirred at a speed of 800r / min for 2 hours, and finally freeze-dried at -20 degrees Celsius to obtain modified nano zinc oxide.
[0044] Preparation of silicon carbide composite powder:
[0045] 100 g of silicon carbide ultrafine powder was mixed with 35 g of modified nano zinc oxide, dried at 110°C for 12 h, mixed with 200 g of anhydrous ethanol and 500 g of deionized water, the pH value of the system was adjusted to 3.5 with hydrochloric acid, ultrasonicated for 30 min, 8 g of KH550 was added, magnetically stirred for 4 h in an oil bath at 50°C, filtered, washed with deionized water, dried in an oven at 100°C for 4 h, and ground to obtain silicon carbide composite powder.
[0046] Preparation method of silicon carbide ceramic 3D printing products:
[0047] S1. Add 110 g of silicon carbide composite powder, 12 g of phase change composite material, 0.5 g of dispersant, 1 g of binder, 0.5 g of plasticizer, 1 g of defoamer, 1 g of water reducer, and 10 g of additive to 100 g of deionized water, and ball mill in a ball mill at a speed of 300 r / min for 24 h to obtain a slurry with a viscosity of 600 mpa·s;
[0048] S2, set the centrifugal turntable speed of centrifugal spray granulation to 10000r / min, the granulation inlet temperature to 250℃, the outlet temperature to 110℃, and perform centrifugal spray granulation on the slurry to obtain a water content of 0.5-1.5%, a fluidity of 4.5-6s, and a bulk density of 0.8-0.95g / cm 3 , the powder repose angle is 30-31°, the particle size distribution is 100-150μm, and the powder morphology maintains more than 99% of the treated powder;
[0049] S3, sieving the treated powder to retain powder between 120-200 meshes;
[0050] S4, placing the sieved powder in a graphite crucible, and transferring the whole to a vacuum sintering furnace, heating it to 200°C, keeping it warm for 2 hours, then evacuating it to -0.1Mpa, heating it to 2000°C at 5°C / min, keeping it warm for 4 hours, to obtain sintered powder;
[0051] S5: Mix the sintered powder with 1.13 g of curing agent and 15.82 g of furan resin and print to obtain a density of 2.05 g / cm 2 The biscuit has no layer pattern or sand deficiency.
[0052] S6, placing the formed green billet into a gas pressure furnace, filling it with nitrogen, adjusting the pressure in the gas pressure furnace to -0.05Mpa, and maintaining the pressure, while keeping the gas flow, to obtain a pre-treated green billet;
[0053] S7. Heat the pretreated green body to 800°C at a rate of 1°C / min, bury 97.18 g of granular silicon with a particle size of 5-10 mm around the pretreated green body, continue to heat to 1400°C, keep warm for 10 minutes, heat to 1750°C at a rate of 2°C / min, keep warm for 4 hours, then cool to 1450°C at a rate of 1°C / min, keep warm for 2 hours, and obtain a silicon carbide ceramic product. Example 2
[0054] Preparation of phase change composite materials:
[0055] In a water bath at 70°C, 5 g of urea, 8 g of melamine, and 12 g of a 37% formaldehyde solution were mixed, 30 g of deionized water was added, and the pH value of the system was adjusted to 8 using triethanolamine. The mixture was stirred at a speed of 300 r / min for 1 hour, then cooled to 25°C, and 20 g of deionized water was added and stirred for 10 minutes to obtain a prepolymer material. 8.68 g of Tween 80, 9.79 g of Span 80, and 1.53 g of sodium sulfate were mixed to obtain a composite emulsifier. In a water bath at 80°C, 5 g of n-octadecane was mixed with the composite emulsifier, 20 g of deionized water was added, and the mixture was stirred at a speed of 300 r / min for 10 minutes. n, continue to add 10g of deionized water, continue stirring for 20min, cool to 25℃ and ultrasonicate for 20min to obtain an emulsion system; under 60℃ oil bath conditions, mix 22g of prepolymer material with 18g of emulsion system, stir at 600r / min for 30min, add 10% mass fraction of citric acid solution to adjust the pH value of the system to 2.5, stir for 30min, heat to 90℃, continue stirring and react for 2h, cool to 25℃, centrifuge at 200r / min for 10min, filter and wash alternately with deionized water and anhydrous ethanol for 3 times, dry in a vacuum drying oven at 40℃ for 8h to obtain a phase change composite material.
[0056] Preparation of modified nano zinc oxide:
[0057] Boron powder, iron oxide and ammonium chloride were mixed in a molar mass ratio of 2:1:1, heated at 600°C for 16 hours, washed alternately with hydrochloric acid and deionized water to remove impurities, and then vacuum dried at 65°C for 4 hours to obtain boron nitride nanotubes; 8.5g of hexadecyltrimethylammonium bromide was mixed with 600g of deionized water, ultrasonicated for 3 minutes, and then 12.41g of boron nitride nanotubes and 37.59g of nano zinc oxide were added, stirred at 800r / min for 2 hours, and finally freeze-dried at -20 degrees Celsius to obtain modified nano zinc oxide.
[0058] Preparation of silicon carbide composite powder:
[0059] 100 g of silicon carbide ultrafine powder was mixed with 45 g of modified nano zinc oxide, dried at 110°C for 12 h, mixed with 200 g of anhydrous ethanol and 500 g of deionized water, the pH value of the system was adjusted to 3.5 with hydrochloric acid, and after ultrasonic treatment for 30 min, 8 g of KH550 was added. The mixture was magnetically stirred for 4 h in an oil bath at 50°C, filtered, washed with deionized water, dried in an oven at 100°C for 4 h, and ground to obtain silicon carbide composite powder.
[0060] Preparation method of silicon carbide ceramic 3D printing products:
[0061] S1. Add 110 g of silicon carbide composite powder, 12 g of phase change composite material, 0.5 g of dispersant, 1 g of binder, 0.5 g of plasticizer, 1 g of defoamer, 1 g of water reducer, and 10 g of additive to 100 g of deionized water, and ball mill in a ball mill at a speed of 500 r / min for 24 h to obtain a slurry with a viscosity of 1250 mpa·s;
[0062] S2, set the centrifugal turntable speed of centrifugal spray granulation to 30000r / min, the granulation inlet temperature to 220℃, the outlet temperature to 100℃, and perform centrifugal spray granulation on the slurry to obtain a water content of 0.5-1.5%, a fluidity of 4.5-6s, and a bulk density of 0.8-0.95g / cm 3 , the powder repose angle is 30-31°, the particle size distribution is 110-150μm, and the powder morphology maintains more than 99% of the treated powder;
[0063] S3, sieving the treated powder to retain powder between 120-200 meshes;
[0064] S4, placing the sieved powder in a graphite crucible, and transferring the whole to a vacuum sintering furnace, heating to 300°C, keeping warm for 2 hours, then evacuating to -0.1Mpa, heating to 2000°C at 5°C / min, keeping warm for 4 hours, to obtain sintered powder;
[0065] S5: Mix the sintered powder with 1.13 g of curing agent and 22.6 g of furan resin and print to obtain a density of 2.10 g / cm 2 The biscuit has no layer pattern or sand deficiency.
[0066] S6, placing the formed green billet into a gas pressure furnace, filling it with nitrogen, adjusting the pressure in the gas pressure furnace to -0.04Mpa, and maintaining the pressure, while keeping the gas flow flowing, to obtain a pre-treated green billet;
[0067] S7. Heat the pretreated green body to 800°C at a rate of 1.5°C / min, bury 149.84g of granular silicon with a particle size of 5-10mm around the pretreated green body, continue to heat to 1400°C, keep warm for 30min, heat to 1750°C at a rate of 2°C / min, keep warm for 4h, then cool to 1450°C at a rate of 2°C / min, keep warm for 2h, and obtain a silicon carbide ceramic product. Example 3
[0068] Preparation of phase change composite materials:
[0069] In a water bath at 70°C, 5 g of urea, 8 g of melamine, and 12 g of a 37% formaldehyde solution were mixed, 30 g of deionized water was added, and the pH value of the system was adjusted to 8 using triethanolamine. The mixture was stirred at a speed of 300 r / min for 1 hour, then cooled to 25°C, and 20 g of deionized water was added and stirred for 10 minutes to obtain a prepolymer material. 8.88 g of Tween 80, 9.55 g of Span 80, and 1.57 g of sodium sulfate were mixed to obtain a composite emulsifier. In a water bath at 80°C, 5 g of n-octadecane was mixed with the composite emulsifier, 20 g of deionized water was added, and the mixture was stirred at a speed of 300 r / min for 10 minutes. n, continue to add 10g of deionized water, continue stirring for 20min, cool to 25℃ and ultrasonicate for 20min to obtain an emulsion system; under 60℃ oil bath conditions, mix 22g of prepolymer material with 18g of emulsion system, stir at 600r / min for 30min, add 10% mass fraction of citric acid solution to adjust the pH value of the system to 2.5, stir for 30min, heat to 90℃, continue stirring and react for 2h, cool to 25℃, centrifuge at 200r / min for 10min, filter and wash alternately with deionized water and anhydrous ethanol for 3 times, dry in a vacuum drying oven at 40℃ for 8h to obtain a phase change composite material.
[0070] Preparation of modified nano zinc oxide:
[0071] Boron powder, iron oxide and ammonium chloride were mixed in a molar mass ratio of 2:1:1, heated at 600°C for 16 hours, washed alternately with hydrochloric acid and deionized water to remove impurities, and then vacuum dried at 65°C for 4 hours to obtain boron nitride nanotubes; 8.5g of hexadecyltrimethylammonium bromide was mixed with 600g of deionized water, ultrasonicated for 3 minutes, and then 11.24g of boron nitride nanotubes and 38.76g of nano zinc oxide were added, stirred at 800r / min for 2 hours, and finally freeze-dried at -20 degrees Celsius to obtain modified nano zinc oxide.
[0072] Preparation of silicon carbide composite powder:
[0073] 100 g of silicon carbide ultrafine powder was mixed with 40 g of modified nano zinc oxide, dried at 110°C for 12 h, mixed with 200 g of anhydrous ethanol and 500 g of deionized water, the pH value of the system was adjusted to 3.5 with hydrochloric acid, and after ultrasonic treatment for 30 min, 8 g of KH550 was added, and magnetic stirring was performed at 50°C in an oil bath for 4 h. After filtering, the mixture was washed with deionized water, dried in an oven at 100°C for 4 h, and ground to obtain silicon carbide composite powder.
[0074] Preparation method of silicon carbide ceramic 3D printing products:
[0075] S1. Add 110 g of silicon carbide composite powder, 12 g of phase change composite material, 0.5 g of dispersant, 1 g of binder, 0.5 g of plasticizer, 1 g of defoamer, 1 g of water reducer, and 10 g of additive to 100 g of deionized water, and ball mill in a ball mill at a speed of 400 r / min for 24 h to obtain a slurry with a viscosity of 900 mpa·s;
[0076] S2, set the centrifugal turntable speed of centrifugal spray granulation to 20000r / min, the granulation inlet temperature to 235℃, the outlet temperature to 105℃, and perform centrifugal spray granulation on the slurry to obtain a water content of 0.5-1.5%, a fluidity of 4.5-6s, and a bulk density of 0.8-0.95g / cm 3 , the powder repose angle is 30-31°, the particle size distribution is 100-150μm, and the powder morphology maintains more than 99% of the treated powder;
[0077] S3, sieving the treated powder to retain powder between 120-200 meshes;
[0078] S4, placing the sieved powder in a graphite crucible, and transferring the whole to a vacuum sintering furnace, heating to 250°C, keeping warm for 2 hours, then evacuating to -0.1Mpa, heating to 2000°C at 5°C / min, keeping warm for 4 hours, to obtain sintered powder;
[0079] S5: Mix the sintered powder with 1.13 g of curing agent and 19.21 g of furan resin and print to obtain a density of 2.05 g / cm 2 The biscuit has no layer pattern or sand deficiency.
[0080] S6, placing the formed green billet into a gas pressure furnace, filling it with nitrogen, adjusting the pressure in the gas pressure furnace to -0.05Mpa, and maintaining the pressure, while keeping the gas flow, to obtain a pre-treated green billet;
[0081] S7. Heat the pretreated green body to 800°C at a rate of 1°C / min, bury 123.17g of granular silicon with a particle size of 5-10mm around the pretreated green body, continue to heat to 1400°C, keep warm for 20min, heat to 1750°C at a rate of 2°C / min, keep warm for 4h, then cool to 1450°C at a rate of 1°C / min, keep warm for 2h, and obtain a silicon carbide ceramic product. Example 4
[0082] Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the phase change composite material, 9.72 g of Tween 80, 8.57 g of Span 80 and 1.71 g of sodium dodecyl sulfate are used. Example 5
[0083] Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the phase change composite material, 8.29 g of Tween 80, 10.25 g of Span 80 and 1.46 g of sodium dodecyl sulfate are used. Example 6
[0084] Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, sodium dodecyl sulfate is not added when preparing the phase change composite material. Example 7
[0085] Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, 28 g of modified nano zinc oxide is used when preparing the silicon carbide composite powder. Example 8
[0086] Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, 47 g of modified nano zinc oxide is used when preparing the silicon carbide composite powder. Example 9
[0087] Example 9 is based on Example 3. In Example 9, when preparing the silicon carbide composite system, the modified nano zinc oxide is replaced with ordinary nano zinc oxide. Example 10
[0088] Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that the amount of the auxiliary agent added in Example 10 is 12 g. Embodiment 11
[0089] Example 11 is based on Example 3. The difference between Example 10 and Example 3 is that the amount of the auxiliary agent added in Example 11 is 20 g. Example 12
[0090] Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that the amount of additive added in Example 12 is 22 g. Embodiment 13
[0091] Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that the auxiliary agent in Example 13 is magnesium oxide. Embodiment 14
[0092] Example 14 is based on Example 13. The difference between Example 14 and Example 13 is that the amount of magnesium oxide added in Example 14 is 10 g. Embodiment 15
[0093] Example 15 is based on Example 13. The difference between Example 15 and Example 13 is that the amount of magnesium oxide added in Example 15 is 20 g.
[0094] Comparative Example 1
[0095] Comparative Example 1 is based on Example 3, and no auxiliary agent is added in Comparative Example 1.
[0096] Comparative Example 2
[0097] Comparative Example 2 is based on Example 3, and in Comparative Example 2, a phase change composite material is added.
[0098] Comparative Example 3
[0099] Comparative Example 3 is based on Example 3, and in Comparative Example 3, the silicon carbide composite powder is replaced with ordinary silicon carbide powder.
[0100] Performance testing
[0101] The following performance tests were performed on the samples of Examples 1-15 and Comparative Examples 1-3:
[0102] (1) Bending strength test
[0103] The bending strength of the samples was tested according to GB / T 6569-2006 Test method for bending strength of fine ceramics. Each sample was tested three times at room temperature, and the average value was taken. The test results were filled in Table 1.
[0104] (2) Fracture toughness test
[0105] The fracture toughness test of the samples was carried out according to the test standard of "GB / T23806-2009 Test method for fracture toughness of fine ceramics - single-side pre-cracked beam method". Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0106] (3) Thermal conductivity test
[0107] Using "GB / T 39862-2021 Test of thermal conductivity of high thermal conductivity ceramics" as the test standard, the thermal conductivity performance of the samples was tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0108] (4) Density test
[0109] The density of the samples was tested according to the test standard of "GB / T 25995-2010 Test method for density and apparent porosity of fine ceramics". Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0110] Table 1 Performance test of Examples 1-15 and Comparative Examples 1-3
[0111]
[0112] Data analysis
[0113] As shown in Table 1, the bending strength of Examples 1-3 is above 300 MPa, and the fracture toughness is above 4 MPa·m 1 / 2 and above, the thermal conductivity is 190 W / (m·K) and above, and the density is 3.13 g·cm 3 The above indicates that the 3D printed silicon carbide ceramics prepared in the present application have good thermal conductivity and mechanical properties, while the density is improved.
[0114] The mass ratios of Tween 80, Span 80 and sodium dodecyl sulfate in Examples 4 and 5 are not within the range specified in the present application. When the content of sodium dodecyl sulfate is too little, the repulsive force between the droplets of the prepared emulsion is difficult to improve, and the binding rate and effect between the emulsion system and the prepolymer material are reduced, so the stability of the prepared phase change composite material is reduced; when the content of sodium dodecyl sulfate is too much, it will also affect the overall stability of the system.
[0115] In Example 6, sodium dodecyl sulfate was not added, which reduced the overall dispersibility of the emulsion system and affected the bonding effect of the phase change composite material.
[0116] In Examples 7 and 8, when preparing silicon carbide composite powders, the mass ratios of modified nano zinc oxide and silicon carbide ultrafine powder are not within the range specified in the present application. When the content of modified nano zinc oxide is too little, the micro-nano synergistic composite effect in the system is reduced, making it difficult to improve the overall bonding performance of the system, affecting the overall mechanical properties and stability of the product; when the content of modified nano zinc oxide is too much, it is difficult to make enough C react with silicon to generate β-SiC grains, and it is difficult to further promote the void filling of the system. Therefore, the density of the system is reduced, and the performance of the product is reduced.
[0117] In Example 9, nano zinc oxide is replaced by ordinary nano zinc oxide. Ordinary nano zinc oxide is not compounded with boron nitride nanotubes, and its surface energy is difficult to be further improved, and it is difficult to fully contact with various components in the system, so the stability of nano zinc oxide decreases.
[0118] The mass ratios of the additives to the silicon carbide composite powder in Examples 10-12 and Examples 14-15 are not within the range defined in the present application, indicating that adding too much or too little additives will affect the overall performance of the product.
[0119] In Comparative Example 1, no additives were added, and the sintering temperature of the powder was difficult to improve, and the uniformity of the powder particle size after sintering was difficult to improve, thus affecting the overall stability of the product. Therefore, various performances of Comparative Example 1 were reduced.
[0120] In Comparative Example 2, no phase change composite material is added, which reduces the overall thermal stability of the system. It is difficult to further improve the stability of the system during the sintering process, and the thermal conductivity of the product is affected.
[0121] In Comparative Example 3, the silicon carbide composite powder is replaced with ordinary silicon carbide powder. The surface energy of ordinary silicon carbide powder is difficult to be modified, and it is difficult to improve the overall compactness of the micro-nano system composite. Therefore, various performances in Comparative Example 3 are reduced.
[0122] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for improving the performance of silicon carbide ceramic 3D printing products, characterized in that: The steps include: Preparation of phase change composite materials: In a water bath at 70°C, 5 g of urea, 8 g of melamine, and 12 g of a 37% formaldehyde solution were mixed, 30 g of deionized water was added, and the pH of the system was adjusted to 8 using triethanolamine. The mixture was stirred at a speed of 300 r / min for 1 hour, then cooled to 25°C, and 20 g of deionized water was added and stirred for 10 minutes to obtain a prepolymer material. 9.09 g of Tween 80, 9.31 g of Span 80, and 1.6 g of sodium sulfate were mixed to obtain a composite emulsifier. In a water bath at 80°C, 5 g of n-octadecane was mixed with the composite emulsifier, 20 g of deionized water was added, and the mixture was stirred at a speed of 300 r / min for 10 minutes. n, continue to add 10g of deionized water, continue stirring for 20min, cool to 25℃ and ultrasonicate for 20min to obtain an emulsion system; under 60℃ oil bath conditions, mix 22g of prepolymer material with 18g of emulsion system, stir at 600r / min for 30min, add 10% mass fraction of citric acid solution to adjust the pH of the system to 2.5, stir for 30min, heat to 90℃, continue stirring and react for 2h, cool to 25℃, centrifuge at 200r / min for 10min, filter and wash alternately with deionized water and anhydrous ethanol for 3 times, dry in a vacuum drying oven at 40℃ for 8h to obtain a phase change composite material; Preparation of modified nano zinc oxide: Boron powder, iron oxide and ammonium chloride were mixed in a molar mass ratio of 2:1:1, heated at 600°C for 16 hours, washed with hydrochloric acid and deionized water alternately to remove impurities, and then vacuum dried at 65°C for 4 hours to obtain boron nitride nanotubes; 8.5g of hexadecyltrimethylammonium bromide was mixed with 600g of deionized water, ultrasonicated for 3 minutes, and then 10g of boron nitride nanotubes and 40g of nano zinc oxide were added, stirred at a speed of 800r / min for 2 hours, and finally freeze-dried at -20 degrees Celsius to obtain modified nano zinc oxide; Preparation of silicon carbide composite powder: 100 g of silicon carbide ultrafine powder was mixed with 35 g of modified nano zinc oxide, dried at 110° C. for 12 h, mixed with 200 g of anhydrous ethanol and 500 g of deionized water, and the pH of the system was adjusted to 3.5 with hydrochloric acid. After ultrasonic treatment for 30 min, 8 g of KH550 was added, and magnetic stirring was performed at 50° C. in an oil bath for 4 h. After filtering, the mixture was washed with deionized water, dried in an oven at 100° C. for 4 h, and ground to obtain silicon carbide composite powder; Preparation of silicon carbide ceramic 3D printing products: S1. Add 110 g of silicon carbide composite powder, 12 g of phase change composite material, 0.5 g of dispersant, 1 g of binder, 0.5 g of plasticizer, 1 g of defoamer, 1 g of water reducer, and 10 g of additive to 100 g of deionized water, and ball mill in a ball mill at a speed of 300 r / min for 24 h to obtain a slurry with a viscosity of 600 mpa·s; S2, set the centrifugal turntable speed of centrifugal spray granulation to 10000r / min, the granulation inlet temperature to 250℃, the outlet temperature to 110℃, and perform centrifugal spray granulation on the slurry to obtain a water content of 0.5-1.5%, a fluidity of 4.5-6s, and a bulk density of 0.8-0.95g / cm 3 , the powder repose angle is 30-31°, the particle size distribution is 100-150μm, and the powder morphology maintains more than 99% of the treated powder; S3, sieving the treated powder to retain powder between 120-200 meshes; S4, placing the sieved powder in a graphite crucible, and transferring the whole to a vacuum sintering furnace, heating it to 200°C, keeping it warm for 2 hours, then evacuating it to -0.1Mpa, heating it to 2000°C at 5°C / min, keeping it warm for 4 hours, to obtain sintered powder; S5: Mix the sintered powder with 1.13 g of curing agent and 15.82 g of furan resin and print to obtain a density of 2.05 g / cm 2 The biscuit has no layer pattern or sand deficiency. S6, placing the formed green billet into a gas pressure furnace, filling it with nitrogen, adjusting the pressure in the gas pressure furnace to -0.05Mpa, and maintaining the pressure, while keeping the gas flow flowing, to obtain a pre-treated green billet; S7. Heat the pretreated green body to 800°C at a rate of 1°C / min, bury 97.18 g of granular silicon with a particle size of 5-10 mm around the pretreated green body, continue to heat to 1400°C, keep warm for 10 minutes, heat to 1750°C at a rate of 2°C / min, keep warm for 4 hours, then cool to 1450°C at a rate of 1°C / min, keep warm for 2 hours, and obtain a silicon carbide ceramic product.
2. A method for improving the performance of silicon carbide ceramic 3D printing products, characterized in that: The steps include: Preparation of phase change composite materials: In a water bath at 70°C, 5 g of urea, 8 g of melamine, and 12 g of a 37% formaldehyde solution were mixed, 30 g of deionized water was added, and the pH of the system was adjusted to 8 using triethanolamine. The mixture was stirred at a speed of 300 r / min for 1 hour, then cooled to 25°C, and 20 g of deionized water was added and stirred for 10 minutes to obtain a prepolymer material. 8.68 g of Tween 80, 9.79 g of Span 80, and 1.53 g of sodium sulfate were mixed to obtain a composite emulsifier. In a water bath at 80°C, 5 g of n-octadecane was mixed with the composite emulsifier, 20 g of deionized water was added, and the mixture was stirred at a speed of 300 r / min for 10 minutes. n, continue to add 10g of deionized water, continue stirring for 20min, cool to 25℃ and ultrasonicate for 20min to obtain an emulsion system; under 60℃ oil bath conditions, mix 22g of prepolymer material with 18g of emulsion system, stir at 600r / min for 30min, add 10% mass fraction of citric acid solution to adjust the pH of the system to 2.5, stir for 30min, heat to 90℃, continue stirring and react for 2h, cool to 25℃, centrifuge at 200r / min for 10min, filter and wash alternately with deionized water and anhydrous ethanol for 3 times, dry in a vacuum drying oven at 40℃ for 8h to obtain a phase change composite material; Preparation of modified nano zinc oxide: Boron powder, iron oxide and ammonium chloride were mixed in a molar mass ratio of 2:1:1, heated at 600°C for 16 hours, washed with hydrochloric acid and deionized water alternately to remove impurities, and then vacuum dried at 65°C for 4 hours to obtain boron nitride nanotubes; 8.5g of hexadecyltrimethylammonium bromide was mixed with 600g of deionized water, ultrasonicated for 3 minutes, and then 12.41g of boron nitride nanotubes and 37.59g of nano zinc oxide were added, stirred at a speed of 800r / min for 2 hours, and finally freeze-dried at -20 degrees Celsius to obtain modified nano zinc oxide; Preparation of silicon carbide composite powder: 100 g of silicon carbide ultrafine powder was mixed with 45 g of modified nano zinc oxide, dried at 110° C. for 12 h, mixed with 200 g of anhydrous ethanol and 500 g of deionized water, and the pH of the system was adjusted to 3.5 with hydrochloric acid. After ultrasonic treatment for 30 min, 8 g of KH550 was added, and magnetic stirring was performed at 50° C. in an oil bath for 4 h. After filtering, the mixture was washed with deionized water, dried in an oven at 100° C. for 4 h, and ground to obtain silicon carbide composite powder; Preparation of silicon carbide ceramic 3D printing products: S1. Add 110 g of silicon carbide composite powder, 12 g of phase change composite material, 0.5 g of dispersant, 1 g of binder, 0.5 g of plasticizer, 1 g of defoamer, 1 g of water reducer, and 10 g of additive to 100 g of deionized water, and ball mill in a ball mill at a speed of 500 r / min for 24 h to obtain a slurry with a viscosity of 1250 mpa·s; S2, set the centrifugal turntable speed of centrifugal spray granulation to 30000r / min, the granulation inlet temperature to 220℃, the outlet temperature to 100℃, and perform centrifugal spray granulation on the slurry to obtain a water content of 0.5-1.5%, a fluidity of 4.5-6s, and a bulk density of 0.8-0.95g / cm 3 , the powder repose angle is 30-31°, the particle size distribution is 110-150μm, and the powder morphology maintains more than 99% of the treated powder; S3, sieving the treated powder to retain powder between 120-200 meshes; S4, placing the sieved powder in a graphite crucible, and transferring the whole to a vacuum sintering furnace, heating to 300°C, keeping warm for 2 hours, then evacuating to -0.1Mpa, heating to 2000°C at 5°C / min, keeping warm for 4 hours, to obtain sintered powder; S5: Mix the sintered powder with 1.13 g of curing agent and 22.6 g of furan resin and print to obtain a density of 2.10 g / cm 2 The biscuit has no layer pattern or sand deficiency. S6, placing the formed green billet into a gas pressure furnace, filling it with nitrogen, adjusting the pressure in the gas pressure furnace to -0.04Mpa, and maintaining the pressure, while keeping the gas flow flowing, to obtain a pre-treated green billet; S7. Heat the pretreated green body to 800°C at a rate of 1.5°C / min, bury 149.84g of granular silicon with a particle size of 5-10mm around the pretreated green body, continue to heat to 1400°C, keep warm for 30min, heat to 1750°C at a rate of 2°C / min, keep warm for 4h, then cool to 1450°C at a rate of 2°C / min, keep warm for 2h, and obtain a silicon carbide ceramic product.
3. A method for improving the performance of silicon carbide ceramic 3D printing products, characterized in that: The steps include: Preparation of phase change composite materials: In a water bath at 70°C, 5 g of urea, 8 g of melamine, and 12 g of a 37% formaldehyde solution were mixed, 30 g of deionized water was added, and the pH of the system was adjusted to 8 using triethanolamine. The mixture was stirred at a speed of 300 r / min for 1 hour, then cooled to 25°C, and 20 g of deionized water was added and stirred for 10 minutes to obtain a prepolymer material. 8.88 g of Tween 80, 9.55 g of Span 80, and 1.57 g of sodium sulfate were mixed to obtain a composite emulsifier. In a water bath at 80°C, 5 g of n-octadecane was mixed with the composite emulsifier, 20 g of deionized water was added, and the mixture was stirred at a speed of 300 r / min for 10 minutes. n, continue to add 10g of deionized water, continue stirring for 20min, cool to 25℃ and ultrasonicate for 20min to obtain an emulsion system; under 60℃ oil bath conditions, mix 22g of prepolymer material with 18g of emulsion system, stir at 600r / min for 30min, add 10% mass fraction of citric acid solution to adjust the pH of the system to 2.5, stir for 30min, heat to 90℃, continue stirring and react for 2h, cool to 25℃, centrifuge at 200r / min for 10min, filter and wash alternately with deionized water and anhydrous ethanol for 3 times, dry in a vacuum drying oven at 40℃ for 8h to obtain a phase change composite material; Preparation of modified nano zinc oxide: Boron powder, iron oxide and ammonium chloride were mixed in a molar mass ratio of 2:1:1, heated at 600°C for 16 hours, washed with hydrochloric acid and deionized water alternately to remove impurities, and then vacuum dried at 65°C for 4 hours to obtain boron nitride nanotubes; 8.5g of hexadecyltrimethylammonium bromide was mixed with 600g of deionized water, ultrasonicated for 3 minutes, and then 11.24g of boron nitride nanotubes and 38.76g of nano zinc oxide were added, stirred at a speed of 800r / min for 2 hours, and finally freeze-dried at -20 degrees Celsius to obtain modified nano zinc oxide; Preparation of silicon carbide composite powder: 100 g of silicon carbide ultrafine powder was mixed with 40 g of modified nano zinc oxide, dried at 110° C. for 12 h, mixed with 200 g of anhydrous ethanol and 500 g of deionized water, and the pH of the system was adjusted to 3.5 with hydrochloric acid. After ultrasonic treatment for 30 min, 8 g of KH550 was added, and magnetic stirring was performed at 50° C. in an oil bath for 4 h. After filtering, the mixture was washed with deionized water, dried in an oven at 100° C. for 4 h, and ground to obtain silicon carbide composite powder; Preparation of silicon carbide ceramic 3D printing products: S1. Add 110 g of silicon carbide composite powder, 12 g of phase change composite material, 0.5 g of dispersant, 1 g of binder, 0.5 g of plasticizer, 1 g of defoamer, 1 g of water reducer, and 10 g of additive to 100 g of deionized water, and ball mill in a ball mill at a speed of 400 r / min for 24 h to obtain a slurry with a viscosity of 900 mpa·s; S2, set the centrifugal turntable speed of centrifugal spray granulation to 20000r / min, the granulation inlet temperature to 235℃, the outlet temperature to 105℃, and perform centrifugal spray granulation on the slurry to obtain a water content of 0.5-1.5%, a fluidity of 4.5-6s, and a bulk density of 0.8-0.95g / cm 3 , the powder repose angle is 30-31°, the particle size distribution is 100-150μm, and the powder morphology maintains more than 99% of the treated powder; S3, sieving the treated powder to retain powder between 120-200 meshes; S4, placing the sieved powder in a graphite crucible, and transferring the whole to a vacuum sintering furnace, heating to 250°C, keeping warm for 2 hours, then evacuating to -0.1Mpa, heating to 2000°C at 5°C / min, keeping warm for 4 hours, to obtain sintered powder; S5: Mix the sintered powder with 1.13 g of curing agent and 19.21 g of furan resin and print to obtain a density of 2.05 g / cm 2 The biscuit has no layer pattern or sand deficiency. S6, placing the formed green billet into a gas pressure furnace, filling it with nitrogen, adjusting the pressure in the gas pressure furnace to -0.05Mpa, and maintaining the pressure, while keeping the gas flow flowing, to obtain a pre-treated green billet; S7. Heat the pretreated green body to 800°C at a rate of 1°C / min, bury 123.17g of granular silicon with a particle size of 5-10mm around the pretreated green body, continue to heat to 1400°C, keep warm for 20min, heat to 1750°C at a rate of 2°C / min, keep warm for 4h, then cool to 1450°C at a rate of 1°C / min, keep warm for 2h, and obtain a silicon carbide ceramic product.
Citation Information
Patent Citations
Manufacturing method of binder jet printing silicon carbide ceramic composite material
CN114920565A
Preparation method of binder jet printing silicon carbide ceramic material
CN115286394A